PENGARUH LATIHAN PASSING AKTIF SEGITIGA TERHADAP AKURASI PASSING PADA PEMAIN LABSCHOOL FUTSAL ACADEMY PADANG - Muhammad Fadli ,; Alimuddin,; Didin Tohidin,; Hadi Pery Fajri , (Jurnal IKEOR, 2023)
The problem of this research is that the passing accuracy of Labschool Futsal Academy Padang players is still low. This study aims to determine whether there is an effect of active triangular passing exercises on passing accuracy in Labschool Futsal Academy Padang players. This type of research is quasi-experimental with data collection techniques using observation. The population in this study were 16 Labschool Futsal Academy Padang players. Samples taken from the results of "total sampling". The instrument used was the passing test on Dermawan futsal (2016). Data analysis using SPSS 22. Based on the results of research on the effect of active triangular passing exercises on passing accuracy in Labschool Futsal Academy Padang players it is known that the pre-test average value is 14.12, the standard deviation is 1.89 and the post-test average value is 17 .93, a standard deviation of 1.98 with an increase of 26.98%. Based on the pre-test and post-test values ​​using the t-paired sample test, it was obtained t count 28.038 > t table 1.753. The results showed that there was an effect of active triangular passing exercises on passing accuracy for Labschool Futsal Academy Padang players